Students’ Perceptions Using Slido Application as Learning Media for Social Sciences in a Primary School Students - Maftucha, Maftucha (Jurusan Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This research is driven by the subdued classroom atmosphere, evidenced by a lack of student motivation to engage in learning, minimum participation in discussions, and numerous instances of late assignment submissions. Consequently, the author tried to address this issue. Slido, a contemporary learning media and evaluation platform, ultimately provided a solution. This research investigates the perceptions of UIN SATU Tulungagung students regarding the Slido application as a learning medium for the subject of learning IPS for MI/SD. The researcher employs descriptive research with a qualitative approach that aims to elucidate the phenomenon in depth and comprehensively. The participants in this study are 32 students of class B from the fifth semester of the PGMI program during the second semester of the 2023-2024 academic year. Data collection techniques included interviews, observations, and documentation. The validity test utilized triangulation and was analyzed using the methods of Mike and Huberman analysis. The findings indicated that students held a positive perception of the Slido application. This research aligns with the ongoing digitalization of learning initiatives. Future researchers are encouraged to investigate a broader range of digital platforms to advance national education.